2014
DOI: 10.1103/physrevb.89.035103
|View full text |Cite
|
Sign up to set email alerts
|

Phases of correlated spinless fermions on the honeycomb lattice

Abstract: We use exact diagonalization and cluster perturbation theory to address the role of strong interactions and quantum fluctuations for spinless fermions on the honeycomb lattice. We find quantum fluctuations to be very pronounced both at weak and strong interactions. A weak second-neighbor Coulomb repulsion $V_2$ induces a tendency toward an interaction-generated quantum anomalous Hall phase, as borne out in mean-field theory. However, quantum fluctuations prevent the formation of a stable quantum Hall phase bef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
107
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 59 publications
10
107
2
Order By: Relevance
“…Despite the fact that we have not found evidence for the Chern insulator (CI) phase, it is still possible that it is realizable in the thermodynamic limit. Different approaches such as cluster mean field 31 can also prove useful to ascertain the presence of the CI phase. We hope that the conclusions of this work will motivate further explorations of the extended Hubbard model on the honeycomb lattice.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that we have not found evidence for the Chern insulator (CI) phase, it is still possible that it is realizable in the thermodynamic limit. Different approaches such as cluster mean field 31 can also prove useful to ascertain the presence of the CI phase. We hope that the conclusions of this work will motivate further explorations of the extended Hubbard model on the honeycomb lattice.…”
Section: Discussionmentioning
confidence: 99%
“…A major obstacle is that, instead of triggering the desired spontaneous TRS breaking, strong interactions tend to stabilize competing solid orders by breaking the translational or rotational lattice symmetry. Thus, the putative topological phase is usually preempted by various competing states [31][32][33][34][35][36]. Moreover, it is also technically challenging to detect such exotic phases with spontaneous TRS breaking, as the TRS partners usually tend to couple on finite-size systems.…”
mentioning
confidence: 99%
“…This subject has attracted vigorous research due to support from mean-field studies, followed by low-energy renormalization-group analysis [13,16], and the existence of such topological phases has been suggested for the extended Hubbard model on various lattice models [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However, unbiased numerical simulations, such as exact diagonalization (ED) and density-matrix renormalization-group (DMRG) studies, found competing states other than topological phases as the true ground states in all previously proposed systems with Dirac points [31][32][33][34] or quadratic band touching points [35,36]. A major obstacle is that, instead of triggering the desired spontaneous TRS breaking, strong interactions tend to stabilize competing solid orders by breaking the translational or rotational lattice symmetry.…”
mentioning
confidence: 99%
“…In particular, one does not want to rely on a purely interaction-driven spin-orbit coupling to generate the Chern insulator phase. 50 The magnetic order that appears above a critical value of U is another important feature of our results. The configurations of local moments under the CDMFT calculations are non-collinear in both bilayer and trilayer systems and they highly resemble their counterparts in the bulk material with the same tight-binding parameters, though they are different in detail because of the lowered symmetry of the films.…”
Section: Discussionmentioning
confidence: 72%
“…For Chern insulators induced "purely" by electron-electron interactions (that is, the underlying Hamiltonian has no intrinsic spin-orbit coupling at the non-interacting level), it appears that temporal fluctuations can indeed destroy the topological phase. 50 In our model-that does include a finite spinorbit coupling at the non-interacting level-we reach the opposite conclusion: Temporal fluctuations do not generally destroy an interaction-driven topological phase in two-dimensions.…”
Section: Introductionmentioning
confidence: 77%